Pengaruh Likuiditas, Leverage, Dan Pertumbuhan Penjualan Terhadap Financial Distress Perusahan Otomotif - Irsa Muna, Chasyta; Gustary, Melly; Chyntia; Susilo Jahja, Adi (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
This study aims to understand the relationship between financial difficulty, liquidity, leverage, and sales growth in manufacturing companies in various industries. This study will focus on Bursa Efek Indonesia-listed automotive and component subsectors. Companies listed in BEI from 2020 to 2022 are the focus of research. Purposive sampling is used to choose samples from companies that meet criteria. Using descriptive statistics and linier berganda analysis, data is analysed. This study shows a link between sales growth, leverage, and liquidity in the financial crisis. The Bursa Efek Indonesia subsector otomotif and component companies see a positive impact from leverage on financial distress, while likuidity and parsial growth have negative effects.